Ultra-violet radiation-cured biofiber composites from kenaf: The effect of montmorillonite on the flexural and impact properties - Rozman, H. D.; Rozyanty, Abdul Rahman; Luqman, Musa; G. S. Tay (Taylor & Francis, 2010)
Link to publisher's homepage at http://www.taylorandfrancisgroup.com/